2019
DOI: 10.1186/s12913-019-4731-8
|View full text |Cite
|
Sign up to set email alerts
|

New understanding of primary health care nurse practitioner role optimisation: the dynamic relationship between the context and work meaning

Abstract: BackgroundOptimising health professionals’ contribution is an essential step in effective and efficient health human resources utilisation. However, despite the considerable efforts made to implement advanced practice nursing roles, including those in primary care settings (PHCNP), the optimisation of these roles remains variable. In this investigation, we report on the subjective work experience of a group of PHCNPs in the province of Quebec (Canada).MethodsWe used Giddens’ structuration theory to guide our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 37 publications
1
20
0
2
Order By: Relevance
“…This is in accordance with previous studies which show that shifting tasks from physicians to NPs is challenging and often met with skepticism. 8,29,30 In addition, to successfully shift tasks, it is essential to have knowledge about NPs' competence before implementing the new role. 8,[30][31][32] Other findings from previous studies also showed that when GPs had experience working with an NP they had a more positive view of task shifting.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previous studies which show that shifting tasks from physicians to NPs is challenging and often met with skepticism. 8,29,30 In addition, to successfully shift tasks, it is essential to have knowledge about NPs' competence before implementing the new role. 8,[30][31][32] Other findings from previous studies also showed that when GPs had experience working with an NP they had a more positive view of task shifting.…”
Section: Discussionmentioning
confidence: 99%
“…We screened 18257 records and considered 283 full texts for inclusion in this integrative review. Fifty-six papers met the inclusion criteria (20,21,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)22,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)23,(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)24,(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)25,(70)(71)(72)(73)(74)…”
Section: Characteristic Of the Included Studiesmentioning
confidence: 99%
“…Studies were conducted across thirteen countries: nine studies in Oceania (26,32,35,44,60,66,(68)(69)(70), one in Asia ( 36), twenty-one in Europe (20,21,(51)(52)(53)(54)57,58,62,65,67,73,22,74,29,33,34,(41)(42)(43)46), twenty-four in North America (23,24,40,45,(47)(48)(49)(50)55,56,59,61,25,64,71,72,75,27,28,30,…”
Section: Characteristic Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations